Done and dusted : a novel - Sage, Lyla (Sage, Lyla. Rebel Blue Ranch., 2023)
"For the first time in her life, Clementine "Emmy" Ryder has no idea what she's doing. She's accomplished everything on her to-do list. She left her small hometown of Meadowlark, Wyoming; went to college; and made a career for herself by doing her favorite thing: riding horses. But after an accident makes it impossible for her to get back into the saddle, she has no choice but to return to the hometown she always wanted to escape. Luke Brooks is Meadowlark's most notorious bad boy, bar owner, and bachelor. He's also the unofficial fifth member of the Ryder family. As Emmy's older brother's best friend, Luke spent most of his childhood antagonizing her. It's been years since he's seen her, but when she walks into his bar and back into his life, he can't take his eyes off her. Despite his better judgment, he wants to do a whole lot more than just look at her. Emmy's got too much on her mind to think about romance. And Luke knows he should stay away from his best friend's younger sister. But what if Luke is just what Emmy needs to get her spark back? Or will they both go up in flames?"--